39‐1: A Low‐Power Reflective LCD Based on a‐Si:H TFT Process. Issue 1 (29th May 2019) - Wang, Lei; Zhang, Mingwei; Zhou, Liang; Kong, Xiangjian; Liu, Jine; Qin, Feng
Abstract : Developed a 1.28inch 64‐color low‐power reflective LCD based on the a‐Si:H TFT process. This display achieves a minimum frame rate of 1 Hz and a corresponding power consumption of less than 75 uW. The maximum frame rate is 58 Hz, at which a smooth dynamic picture can be displayed. We overcome the flicker issue of low frame rate by adopting new pixel and drive design. After 240 hours of 60 ° C / 90% RH dynamic reliability testing, the flicker is still within the visually acceptable range.